Cross validation of the aerodynamic and acoustic measurements in two Kevlar-walled wind tunnels. Issue 2 (1st May 2022) - Fischer, Andreas; Bak, Christian; Lylloff, Oliver; Olsen, Anders S.; Mikkelsen, Robert F.; Ildvedsen, Sigurd B.; Beckerlee, Jimmy S.; Borgoltz, Aurelien; Kuester, Matthew; Intaratep, Nanyaporn
Abstract: The wind tunnel with Kevlar walls is becoming more and more popular for aeroacoustic measurements, because the necessary corrections to convert aerodynamic coefficients to free field values are moderate and at the same time the signal to noise ratio of acoustic measurements are in the same order as in an open jet configuration. Yet, the technology is new and the correction methods for aerodynamic and acoustic coefficients are not well established. This paper aims on bench-marking two of the largest Kevlar-walled wind tunnels by cross validation of the measurements performed on a NACA633 018 aerofoil model. The measured aerodynamic coefficients showed and excellent agreement in the attached flow regime. Maximum lift was predicted differently in the two facilities. The differences might be due to three-dimensional effects for separated flow and the fact that the aspect ration was different in the two facilities. The difference of the measured overall sound pressure levels was less ± 1 dB for attached flow conditions. However, we observed a difference in the slope of the sound pressure spectra and recommend to further investigate the acoustic correction methods.